Establishment of the ACPHEED in the Three Host Countries - Indonesia, Thailand, and Viet Nam: A Win-Win Solution? - Thaiprayoon, Suriwan; Winothai, Mayuree; Kaewpramkusol, Ratchakorn; Tangcharoensathien, Viroj; Wibulpolprasert, Suwit; Patcharanarumol, Walaiporn (Journal of Health Science of Thailand, 2024)
The unprecedent impact of the COVID-19 pandemic on socio-economic development of the ASEAN region prompted its member states to create a regional centre to respond to public health emergencies and emerging diseases. A feasibility study of establishing this center was conducted in mid-2020 and the result confirmed the feasibility of the establishment of the ASEAN Centre for Public Health Emergencies and Emerging Diseases (ACPHEED). Later, the ASEAN Leaders officially announced the establishment of the ACPHEED at the 37th ASEAN Summit held in November 2020. Subsequently, several ASEAN member states, including Thailand, have expressed their interest to host the ACPHEED. The number of the ASEAN Senior Officials’ Meetings on Health Development were convened to discuss and negotiate on the selection of the host country. These deliberations had lasted for almost two years before consensus was reached to establish the ACPHEED in three host countries: Thailand, Indonesia, and Vietnam, with the establishment of the ACPHEED Secretariat Office in Thailand. Before reaching this consensus, the competing countries negotiated intensively before adjusting their negotiation strategy from “position-based negotiation” to “Interest-based negotiation”, until achieving an outcome that all parties were satisfied with. This article builds on our first paper on “ASEAN Centre for Public Health Emergencies and Emerging Diseases: Thailand’s proposal” published in ths Journal in December 2022, aiming to present an evolution of the selection process of the ACPHEED host country, including strategic negotiations used in this process led to a success in reaching consensus. We draw lessons learned from this process as part of capacity development on global health of Thailand officials for future international negotiations.